Hepatocyte nuclear factor 4α in the pathogenesis of non-alcoholic fatty liver disease - Xiaoli Pan; Yanqiao Zhang; Yuanyuan Ji (Chinese Medical Journal, 2022)
Abstract. Non-alcoholic fatty liver disease (NAFLD) is emerging as the most common chronic liver disease worldwide. It refers to a range of liver conditions affecting people who drink little or no alcohol. NAFLD comprises non-alcoholic fatty liver and non-alcoholic steatohepatitis (NASH), the more aggressive form of NAFLD. NASH is featured by steatosis, lobular inflammation, hepatocyte injury, and various degrees of fibrosis. Although much progress has been made over the past decades, the pathogenic mechanism of NAFLD remains to be fully elucidated. Hepatocyte nuclear factor 4α (HNF4α) is a nuclear hormone receptor that is highly expressed in hepatocytes. Hepatic HNF4α expression is markedly reduced in NAFLD patients and mouse models of NASH. HNF4α has been shown to regulate bile acid, lipid, glucose, and drug metabolism. In this review, we summarize the recent advances in the understanding of the pathogenesis of NAFLD with a focus on the regulation of HNF4α and the role of hepatic HNF4α in NAFLD. Several lines of evidence have shown that hepatic HNF4α plays a key role in the initiation and progression of NAFLD. Recent data suggest that hepatic HNF4α may be a promising target for treatment of NAFLD.